Market Structure, Conduct, and Performance of Indonesian Banking Industry - Mohammad Sofyan; Mintarti Indartini; Amikul Pricilia Maswati Dewi (Universitas Hayam Wuruk Perbanas, 2025)
This study examines the interrelationship between market structure, bank conduct, and financial performance in Indonesia’s commercial banking industry using the Structure–Conduct–Performance (SCP) framework. The analysis focuses on the four largest banks—BCA, BRI, Mandiri, and BNI—over the period 2015–2024, representing a highly concentrated oligopolistic market. Using a balanced panel dataset and fixed-effects regression, this study investigates whether structural dominance, proxied by bank size, influences lending behavior and profitability. The results show that bank size has a positive and significant effect on credit distribution, indicating that larger asset bases enhance intermediation capacity. Credit distribution, in turn, significantly improves profitability as measured by Return on Assets (ROA). However, the direct effect of size on ROA is negative and significant, suggesting the presence of diseconomies of scale. These findings imply that while market structure determines conduct, financial performance is driven more by managerial efficiency and effective credit allocation than by structural dominance alone. The study concludes that the SCP paradigm operates sequentially but not symmetrically in Indonesia’s concentrated banking market. Policy implications emphasize the importance of operational efficiency and credit quality management alongside structural oversight